The NIWA seamount sled: An effective epibenthic sledge for sampling epifauna on seamounts and rough seafloor. (February 2016) - Clark, Malcolm R.; Stewart, Rob
Abstract: Epibenthic sleds, sledges and dredges have been widely used for sampling deep-sea macro and megafaunal communities, providing extensive information on benthic biodiversity and distribution patterns. Different countries and institutes have developed a variety of gear types, but these are often unsuitable for sampling rough seafloor, such as seamount and ridge topography. The NIWA seamount sled, a form of epibenthic sledge, is an inexpensive yet robust and versatile sampling device used to obtain invertebrate and rock samples. It incorporates features from a number of existing designs that have produced a versatile sled that can be used on all habitats from mud through to steep and rocky seamounts. It has been used for many research surveys around New Zealand, where it has proven an efficient sampler of target fauna (large macro- and mega-benthic epifauna). Its design has also been adopted by institutes in France and China for surveying seamounts, and it is suggested it could be used as a simple standardised design for sampling seamounts internationally. Highlights: We describe the design of an epibenthic sled for use on seamounts and rough seafloor. The sled is designed to sample large benthic macrofauna and mega-epifauna. The sled has been used effectively on 90 seamounts in New Zealand over 15 years. It is suggested the design could be a standard for sampling seamounts internationally.